Efektifitas Akupresure dalam Mengatasi Gangguan Tidur pada Menopause - erika, nurlia; sapitri, wiwik; Sofiyanti, Ida (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2023)
Menopause is a process in the natural reproductive cycle that is no longer able to meet the hormone estrogen. Menopause who experience sleep disorders 750 people  year. The prevalence of sleep disorders in Indonesia is quite high, around 50%. The healt problems that are often encountered in menopause are immobilization, postural instability, urinary incontinence, infection, impairment of senses, inanition, iatrogenic, insomnia, intellectual impairment, isolation, impecunity, impation, immune deficiency, and impotence. From the problems mentioned above, there are several problems, that can affect menopause productivity, one of which is insomnia. This community service is carried out in stages, namely selection of menopausal elderly, licensing of village midwives, implementation of activities, evaluation.This service aims to examine the effectiveness of acupressure in overcoming sleep disturbances in menopause. The population of this service is menopause 20 people. This activity uses leaflet media and is carried out oflline (face to face). Abstrak Menopause merupakan suatu proses dalam siklus reproduksi alamiah yang tidak lagi sanggup memenuhi hormon estrogen. Menopouse yang mengalami gangguan tidur 750 orang per tahunnya. Prevalensi gangguan tidur di Indonesia cukup tinggi sekitar 50%.Adapun masalah kesehatan yang sering ditemui pada menopouse adalah immobilisasi, instabilitas postural, inkontinentia urine, infection, impairment of senses, inanition, iatrogenic, insomnia, gangguan intelektual, isolasi, ketidak berdayaan, impasi, defisiensi imun, dan impotence. Dari masalah tersebut di atas, ada beberapa masalah yang bisa mempengaruhi produktifitas menopouse, salah satunya adalah insomnia. Pengabdian masyarakat ini dilakukan dengan tahapan yaitu pemilihan pasien menopause, perizinan pada bidan desa, pelaksanaan kegiatan, evaluasi. Pengabdian ini bertujuan untuk mengkaji efektifitas akupresure dalam mengatasi gangguan tidur pada menopause. Populasi pengabdian ini adalah menopause 20 orang. Kegiatan ini menggunakan media leaflet dan dilakukan secara luring (tatap muka).